Predictive relationship between COVID-19 anxiety and psychological distress in adolescents during the COVID-19 pandemic - McMahon, Jennifer; Dowling, Katherine; Gallagher, Elaine; Donnellan, Alanna; Houghton, Sharon; Ryan, Megan; O’Connor, Cliodhnad; Walsh, Eibhlín (Frontiers in Psychology, 2024)
COVID-19 was a novel stressor that gave rise to pandemic related anxiety and increased the risk of mental health issues, particularly in youth. It is important to understand how such events contribute to psychological distress in young people to adequately intervene in the aftermath and to plan for future similar events. Using cross-sectional data from the CoSPACE Ireland study dataset this paper reports on the predictive relationship between COVID-19 anxiety and psychological distress for Irish adolescents (N = 314, M = 14.05, SD = 2.7, 11–18 years), while controlling for other influencing factors across multiple levels of a bioecological systems approach. Covariates were age, gender, ethnicity, social economic status, Peer Support, School Support and Parent–Child Closeness. Findings indicate that COVID-19 anxiety was a significant predictor of adolescents’ psychological distress. Specifically, Consequence Anxiety (worries about the indirect consequences of COVID-19) was found to be a predictor of adolescents’ psychological distress rather than Disease Anxiety (worries about the COVID-19 virus itself). Individual factors (e.g., age, ethnicity, special educational needs) and microsystem factors (e.g., parent child closeness, peer support) were also found to impact on adolescents’ levels of psychological distress. A significant moderation analysis revealed that greater parent–child closeness reduced the strength of the positive association between Consequence Anxiety and psychological distress. These findings suggest that strategies to alleviate adolescents’ psychological distress during pandemics should focus on reducing pandemic-related anxiety, specifically Consequence Anxiety. A multisystemic approach is also recommended to reduce the negative mental health impacts of the pandemic on adolescents.